Relação produtividade-diversidade em comunidade fitoplanctônica de reservatórios do semiárido nordestino do Brasil - Costa, Davi Freire da (2014)
The relationship between ecosystem productivity and biological diversity or PDR (English "productivity-diversity relationships") has become a research area in ecology that has contributed to increasing knowledge about the functioning of ecosystems. Ecologists have found variations in the shape of PDR, such as positive or negative linear, unimodal “humpshaped” or "U-shaped" and unrelated described. There is evidence that PDR is positive linear in regional scale and unimodal in local scale when the regional dissimilarity in species composition increases with productivity in lagoon systems. However, there are in literature, variations in the PDR in phytoplankton on a local scale, which allows us to suggest that environmental factors may affect this relationship locally. Reservoirs are spatially heterogeneous ecosystems, since they have compartments with conditions ranging from lentic in dam until lotic in tributary. This study aimed to: assess the shape of the PDR in phytoplankton reservoirs in local (compartments) and regional (reservoirs) scale; assess the relationship between regional dissimilarity in species composition and regional average productivity; and test the potential of environmental factors such as productivity measures and other physical and chemical factors as descriptors of phytoplankton diversity on scale spatial adopted. For this, were chosen 23 sampling points distributed in seven reservoirs located in the watershed of the river Paraíba, semi-arid northeast of Brazil. Samples were collected at these points to determine the availability of nutrients (total nitrogen, ammonia, nitrite, nitrate, orthophosphate and total phosphorus), phytoplankton biomass and richness. It was used the nutrient availability and phytoplankton biomass as measures of productivity and species richness as a measure of diversity. Some physical and chemical factors of water, such as temperature, pH, conductivity, turbidity, dissolved oxygen, total dissolved solids and salinity were obtained from field equipment. Regression analyses were performed to verify the shape of the relationship between measures of productivity and diversity, and between regional dissimilarity in species composition and the regional average productivity. Generalized linear models analyses were done to test the potential of environmental factors as descriptors of the richness of phytoplankton. The shape of the PDR did not vary with spatial scale, linear negative and unimodal relationships were observed. The regional dissimilarity decreased with the regional average productivity. The models indicated that local richness was influenced by physical and chemical factors besides productivity measures. It was concluded that the form of PDR was independent of spatial scale using reservoirs as units of study, situation attributed to the effect of eutrophication on reducing the differences between the species composition of the compartments within each reservoir, generating losses in the diversity of these ecosystems. Furthermore, analysis of the models showed indications that the PDR on a local scale can be influenced by physical and chemical environmental factors.